2019
DOI: 10.1094/pdis-07-18-1187-re
|View full text |Cite
|
Sign up to set email alerts
|

Colletotrichum acutatum and C. gloeosporioides Species Complexes Associated with Apple in Brazil

Abstract: Glomerella leaf spot (GLS) is an apple disease that concerns growers due to the increases in severity over the years and the difficulties in control. Species within the Colletotrichum acutatum and C. gloeosporioides species complexes cause GLS, but the proportion of species within each complex in Brazilian apple orchards is not known. The objectives of this study were to identify isolates of Colletotrichum causing GLS on apple orchards in the main Brazilian producing regions to the species level. Two hundred a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
18
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(20 citation statements)
references
References 40 publications
2
18
0
Order By: Relevance
“…The Colletotrichum gloeosporioides was found as a post-harvest pathogen, which caused bitter rot disease in apple fruits. These results are supported by various researches (Grammen et al 2019;Moreira et al 2019 andVelho et al 2014). Fusarium rot and Alternaria rot caused by Fusarium oxysporum and Alternaria alternata, respectively were found during the study.…”
Section: Discussionsupporting
confidence: 84%
“…The Colletotrichum gloeosporioides was found as a post-harvest pathogen, which caused bitter rot disease in apple fruits. These results are supported by various researches (Grammen et al 2019;Moreira et al 2019 andVelho et al 2014). Fusarium rot and Alternaria rot caused by Fusarium oxysporum and Alternaria alternata, respectively were found during the study.…”
Section: Discussionsupporting
confidence: 84%
“…In addition, plants treated with plant extracts are organic and more expensive. However, FRAC (2020) showed that mancozeb caused less risk of resistance development, but some studies have already reported several pathogens (Colletotrichum species) resistant to this multi-site fungicide (Moreira et al, 2019b). The results of the biochemical analyses obtained show that AENS stimulated the activity of enzymes (PPO, POX and Glucanase) in the corn leaves on the one hand, and increased the amount of phenolic compounds and total proteins in the corn leaves on the other hand.…”
Section: Discussionmentioning
confidence: 99%
“…The species C. nymphaeae is known to cause diseases in several species such as the glomerella leaf spot on apple trees (Mallus domestica). In this disease, the fungus attacks leaves and fruit and the symptoms appear as red-purple spots and defoliation (Moreira et al, 2019). In olive (Olea europea), C. nymphaeae attacks fruits at the beginning of their development, causing a dark brown lesion, also affecting the stalk, causing chlorosis and progressing to necrosis and, consequently, their premature fall (Antelmi et al, 2019).…”
Section: Molecular Characterizationmentioning
confidence: 99%